Synthetic Efforts Towards the Lagunamide and Chalcone Based Natural Products - Farleigh, Douglas A. (My University, 2021)
The Lagunamides are a series of secondary metabolites produced by marine cyanobacteria that possess almost identical polypeptide and polyketide moieties and display potency against various cancer cell lines. They are differentiated by the side chain on the polyketide moiety. Chalcones are a class of molecules characterized by an α,β-unsaturated ketone moiety and adjacent phenyl groups; some species that fall under this classification have displayed a similar efficacy when tested against various cancer cell lines. Synthetic procedures on a 100 mg scale and their associated mechanisms regarding the construction of Crimmins’ auxiliaries (yield = 72%), diazotization of D-alloisoleucine (yield = 40%/35% for 300 mg scale), and the esterification (yield = 72%), Boc deprotection (yield = 84%), and first peptide coupling (yield = N/A) in the formation of the polyketide moiety of Lagunamides are discussed. Furthermore, the synthetic procedure and mechanism for the acylation (yield = 24%) and subsequent methylation (yield = N/A) of phloroglucinol are provided. For the unsuccessful peptide coupling reaction, the most likely point of failure was the lack of carboxylic acid activation by EDC. For the unsuccessful acylation of phloroglucinol, consideration of the kinetics of aromatic substitutions and the NMR spectrum of the product indicated that diacylation had occurred (the desired product was monoacylated).